KONSEP PENDIDIKAN ISLAM; Pendekatan Metode Pengajaran - Mumtazul Fikri (Universitas Islam Negeri Ar-Raniry, 2011)
Method of teaching is an art in education, a teaching staff is no different in principle from a guitarist who beautifully plucked guitar string on stage arts, the teacher is an artist who transfer knowledge to students. Method is considered more significant than the subject matter itself. The communicative teaching was more effective and attracting the students even though the material presented was not so interesting. Instead, the material is quite good, as the methods are less attractive, then the material could not be caught by students. Varied and persuasive methods will be motivating students to learn. Besides the success of classroom teaching and learning process is also determined at the level of teachers as sensitive educators to differed characteristics of diverse learners. Intelligent teacher is able to position himself as an educator as well as a parent of children in the classroom learning.